Аlgorithmic and Conceptual Approach to Figure Surface Measurement - Marijana Ž. Zeljić; Milica R. Ivančević (University of Belgrade, Teacher Education Faculty, 2019)
Surface measurement is an important topic of the school curricula which is closely related to other mathematical topics and to the real world. The results of numerous international studies show that students' achievements in the area of surface measurement are low, which is explained by the algorithmic approach to the topic characterised by the emphasis on procedural skills and the application of formulas. The paper looks at different levels and parameters of the conceptual understanding of surface measurement.. The aim of the research is to examine the level and quality of knowledge about surface measurements among pupils of the fourth grade of primary school. The descriptive method and testing technique were used in the research. The test consists of standardised tasks (Huang & Witz, 2013) and two more tasks that are not part of the standardised test and that were designed based on the transcript of the interviews from the above study. The convenience sample consisted of two classes of the fourth-grade pupils of a primary school in Belgrade. The key conclusion is that students have developed an instrumental understanding of the surface measurement procedure and that the strategies for determining the surface of the figures reduce the application of the formula, which is why they choose, often mistakenly, the wrong formula. Based on the research findings, we conclude that more time should be devoted to activities involving the conceptual approach to the division of figures and tiling. These activities will bridge the great gap between surface tiling and counting the units of measure and the understanding of calculation formulas.